AN ANALYSIS OF STUDENTS’ ERROR IN CONSTRUCTING CONTENT QUESTION - Prasadha, Donni; Marbun, Rismaya; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstarct: This research aims to find out errors in constructing content question made by the eleventh grade students of students SMK Bina Putra Sungai Raya Pontianak, to identify the type of errors in constructing content question and to investigate the percentage of the type of error in constructing content question. The method of research that used is a descriptive method. The technique of data collecting is a measurement technique. Sample of the research is 25 students. After having conducted the research, the writer found some fact that the eleventh grade stutents of SMK Bina Putra Pontianak made some errors in constructing content question, most of students could constructed content question well although there were some students still made some errors in constructing content question, there are five aspect that writer analized, those are question word, Auxiliary, Verb, Auxiliary, To be and Compliment. Most of the students made errors in constructing content question, especially in auxilliary and complement aspects with percentage 73% and 64%, that is High. These errors cover on four types of error, they are error of ommision, addition, substitution and ordering. The error of substitution is the most common error of all. Key word: Analysis, Error, Constructing, Content Question Â Abstrak: Penelitian ini bertujuan untuk menemukan kesalahan siswa kelas XI SMK Bina Putra Sungai Raya Pontianak dalam membuat content question, untuk mengidentifikasi tipe kesalahan dalam membuat content quention, dan untuk mengetahui persentase kesalahan dalam membuat content quention. Metode yang digunakan dalam penelitian ini adalah metode deskriptif. Sedangkan teknik pengumpulan data menggunakan teknik pengukuran. Penelitian ini menggunakan sampel yang berjumlah 25 siswa. Setelah melakukan penelitian penulis menemukan beberapa fakta bahwa siswa kelas XI SMK Bina Putra Pontianak melakukan beberapa kesalahan dalam membuat content quention. Kebanyakan siswa bisa membuat content quention dengan baik, akan tetapi ada beberapa siswa yang masih melakukan beberapa kesalahan dalam membuat content quention.Â Ada lima aspek yang penulis analisis, yaitu question word, Auxiliary, Verb, Auxiliary, To be dan Compliment. Kebanyakan siswa membuat kesalahan pada aspek Auxiliary dan Compliment dengan persentase 73% dan 64% dengan kualifikasi tinggi. Kategori kesalahan mencakup empat tipe kesalahan, yaitu ommision, addition, substitution and ordering. Tipe kesalahan subtitution adalah tipe kesalahan yang sering dilakukan oleh siswa. Kata kunci: Analisis, Kealahan, Membuat, Kalimat Tanya